Structural Behaviour of Precast Concrete Sandwich Panels with Openings Under Axial Load - Abdul Aziz, Farah Nora Aznieta (2002)
This research was conducted to study the structural behaviour of precast concrete sandwich panels with opening. Four types of sandwich panels involving panels without opening, panels with door opening, panels with window opening and panels with both door and window opening were studied. The size of the panels was 900mm x l000mm x 120mm thick. The 120mm thickness consists of two concrete layers with a sandwich insulation layer 40mm thick. The panels were tested under axial load until failure. During the experiment, the development of cracks was observed and the strain and dial gauges reading recorded. The values of experimental ultimate load for the panel without opening were compared to the theoretical ultimate load by a few researchers. For panels with opening, the experimental ultimate loads were compared to the theoretical equation for panels with opening by Saheb and Desayi. The theoretical equation used was actually meant to estimate the ultimate load of ordinary reinforced concrete walls with opening. It was used in sandwich panels with the assumption that the total thickness of the panels was equal to the thickness of the concrete layers only. From the calculations it was found that the theoretical equation by Saheb and Oesayi for the ultimate load of ordinary reinforced concrete walls with opening gave very close values to the experimental results for panels with opening. This showed that the ultimate load equation for ordinary reinforced concrete wall with opening by Saheb and Desayi could be used to estimate the ultimate load of sandwich panels with opening. Beside the ultimate load, the lateral deflection and the strain distribution in the reinforcement and concrete surface were also observed and recorded.